1981
DOI: 10.1038/jcbfm.1981.12
|View full text |Cite
|
Sign up to set email alerts
|

Direct Vascular Effects of Agents Used in the Pharmacotherapy of Cerebrovascular Disease on Isolated Cerebral Vessels

Abstract: Summary:The direct vasomotor effects of a number of agents used in the therapy of cerebral circulatory and metabolic disease were studied in isolated segments of cat pial vessels in vitro, Studies were repeated eight times gener ally, thus permitting the calculation of the mean maximum response-termed ifenprodil > vincamine > nicergoline > dihydroergotoxine > raubasine, In addition, it was considered worthwhile to determine whether the ifenprodil induced vasoconstriction occurred when human, rather than cat, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…F e Effect of TCN-201 pretreatment on CSD (no significant difference with corresponding control). studies on isolated cerebral vessels (Young et al, 1981). However, other in-vitro studies suggested the anti-vasoconstrictive effect of Ifenprodil (Arai et al, 1991) (McCool andLovinger, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…F e Effect of TCN-201 pretreatment on CSD (no significant difference with corresponding control). studies on isolated cerebral vessels (Young et al, 1981). However, other in-vitro studies suggested the anti-vasoconstrictive effect of Ifenprodil (Arai et al, 1991) (McCool andLovinger, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Ifenprodil is an α1 adrenergic receptor antagonist that was originally developed as a vasodilator. 61 It was subsequently found to be a highly selective antagonist of the NMDA GluN2B subunit. 62 Upon ifenprodil binding, the bi-lobed structure of the GluN2 amino-terminal domain adopts a closed conformation, accompanied by rearrangement of the GluN1–GluN2 amino-terminal domain heterodimeric interface to inhibit receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ifenprodil has also been demonstrated to have some vasodilator effects via ␣-adrenoceptors, 9 and it is also known to constrict pial vessels. 48 These properties may result in an inverse steal phenomenon in which blood flow is diverted from the normal tissue toward the ischemic focus. 21 However, we did not observe any change in either mean ABP or CBF between saline-and ifenprodil-treated groups during ischemic and reperfusion periods.…”
Section: Fig 3 Drawings Illustrating Infarction In the Brains Of Ifen-mentioning
confidence: 99%